Bayesian default probability models - Petra Andrlíková (Charles University in Prague, Institute of Economic Studies (IES), 2014)
This paper proposes a methodology for default probability estimation for low default portfolios, where the statistical inference may become troublesome. The author suggests using logistic regression models with the Bayesian estimation of parameters. The piecewise logistic regression model and Box-Cox transformation of credit risk score is used to derive the estimates of probability of default, which extends the work by Neagu et al. (2009). The paper shows that the Bayesian models are more accurate in statistical terms, which is evaluated based on Hosmer-Lemeshow goodness of fit test, Hosmer et al. (2013).
Keywords: C11; C51; C52; G10; 330; default probability; bayesian analysis; logistic regression; goodness-of-fit